Distinct Expression Pattern of a Deafness Gene, KIAA1199, in a Primate Cochlea. (14th June 2016) - Hosoya, Makoto; Fujioka, Masato; Okano, Hideyuki; Ogawa, Kaoru
Abstract : Deafness is one of the most common types of congenital impairments, and at least half of the cases are caused by hereditary mutations. Mutations of the gene KIAA1199 are associated with progressive hearing loss. Its expression is abundant in human cochlea, but interestingly the spatial expression patterns are different between mouse and rat cochleae; the pattern in humans has not been fully investigated. We performed immunohistochemical analysis of a nonhuman primate, common marmoset ( Callithrix jacchus ), cochlea with a KIAA1199-specific antibody. In the common marmoset cochlea, KIAA1199 protein expression was more widespread than in rodents, with all epithelial cells, including hair cells, expressing KIAA1199. Our results suggest that the primate pattern of KIAA1199 expression is wider in comparison with rodents and may play an essential role in the maintenance of cochlear epithelial cells.